Primary Cell Cultures in Neurobiology: Optimized Protocol for Culture of Mouse Fetal Hindbrain Neurons - Hadrien Glibert; Laure Bridoux; Maëlle Palate; Coralie Piget; Marie-Thérèse Ahn; Roberta Gualdani; Ana Domínguez-Bajo; Frédéric Clotman; Filippo M. Rijli; Françoise Gofflot (Cells)
Primary cultures of neural cells are important key tools for basic and translational neuroscience research. These primary cell cultures are classically generated from the rodent brain hippocampus or cortex and optimized for enrichment in neurons at the expense of glial cells. Importantly, considerable differences exist in neuronal cell populations and in glial cell contribution between different brain regions. Because many basic and translational research projects aim to identify mechanisms underlying brainstem neuronal networks that affect major vital functions, primary cultures representative of cell populations present in the hindbrain are required. However, the preparation of primary cultures of brainstem/hindbrain neurons is scarcely described in the literature, limiting the possibilities for studying the development and physiology of these brain regions in vitro. The present report describes a reliable protocol to dissociate and culture in vitro embryonic mouse fetal hindbrain neurons in a defined culture medium, while control of astrocytes’ expansion was attained by using a chemically defined, serum-free supplement, namely CultureOne™. The neuronal cells maintained according to this protocol differentiate and, by 10 days in vitro, they develop extensive axonal and dendritic branching. Using immunofluorescence, we further characterized the different cell populations and neuronal subtypes. Patch–clamp recordings demonstrate the excitable nature of these neurons, while colocalization of pre- and postsynaptic neuronal markers showed that neurons form mature synapses, suggesting the establishment of functional networks in vitro. The cultures produced by this method show excellent reproducibility and can be used for molecular, biochemical, and physiological analyses, as illustrated here for tamoxifen-induced Cre recombination in genetically-modified neural cells.